Structural, Optical and Electrical Properties of Europium Picrate Tetraethylene Glycol Complex as Emissive Material for OLED - Kusrini, E.; Saleh, M.I.; Adnan, R.; Yulizar, Y.; Shiong, N.S.; Fun, H.K.; Adhha Abdullah, M.A.; Mamat, M.; Za'aba, N.K.; Abd Majid, Wan Haliza (2012)
A new europium complex Eu(Pic) 2(H 2O)(EO4)(Pic) Â·0.75H 2O was synthesized and used as the emission material for the single layer device structure of ITO/EO4EuPic/Al, using a spin-coating technique. Study on the optical properties of the Eu(Pic) 2(H 2O)(EO4)(Pic)Â·0.75H 2O complex where EO4=tetraethylene glycol and Pic=picrate anion, had to be undertaken before being applicable to the study of an organic light emitting diode (OLED). The electrical property of an OLED using currentvoltage (IV) measurement was also studied. In complex, the Eu(III) ion was coordinated with the EO4 ligand as a pentadentate mode, one water molecule, and with two Pic anions as bidentate and monodentate modes, forming a nine-coordination number. The photoluminescence (PL) spectra of the crystalline complex in the solid state and its thin film showed a hypersensitive peak at 613.5614.9 nm that assigned to the 5D 0â 7F 2 transition. A narrow band emission from the thin film EO4EuPic was obtained. The typical semiconductor IV curve of device ITO/EO4EuPic/Al showed the threshold and turn on voltages at 1.08 and 4.6 V, respectively. The energy transfer process from the ligand to the Eu(III) ion was discussed by investigating the excitation and PL characteristics. Effect of the picrate anion on the device performance was also studied. Â© 2011 Elsevier B.V. All rights reserved.